The pre-nesting behaviour of the Greenland White-fronted Goose - Fox, A D; Madsen, J (Wildfowl, 1981)
Greenland White-fronted Geese Anser albifrons flavirostris were observed feeding for up to ten days between the peak period of arrival and the onset of nesting in west Greenland. Birds fed on highly nutritious subterranean plant perenniating organs for 68% of their diurnal activity, roosting only during the period of sub-zero temperatures. Attendant vigilant ganders in solitary pairs enabled female geese to feed for maximal, uninterrupted periods. The males gained advantage from joining flocks of other geese, spending less time alert with a corresponding increase in the proportion of their time spent feeding, although there appeared no advantage to females in social feeding.